Peer Review of JMH Volume 1 Number 5 February 2017 - Team, Editorial (Journal of Medicine and Health, 2017)
We would like to thank our peer reviewers for the precious contributions in providing clinical,scientific, and methodological expertise for JMH Volume 1 Number 5. We appreciate everythoughtful review of submitted manuscripts and for making important contributions to improve thescientific quality of articles published in JMH. We listed the names in alphabetical order.dr.Decky Gunawan,M.Kesdr. Djaja Rusmana, M.Sidr.Fari,Sp.THTdr. Fenny, Sp.PKdr. Hanna, M.Kes., PhD., AIFOProf. Dr. Ida Parwati, dr, SpPK(K), PhDProf.dr. Jeanne A. Pawitan, MS, PhDdr. July Ivone,MKK.,M.Pd.KedDr. dr. Meilinah Hidayat, M.Kesdr. Mia Kusmiati,M.Pd.KedDr. dr. Oeij Anindita Adhika, M.Kes., PA(K)Prof.Dr. Ridad Agoes,MPHdr. Rizna T.Rumanti,M.Kesdr. Ronny Lesmana,M.Kes, AIFO, Ph.Ddr. Roro Wahyudianingsih, Sp.PAdr. Sylvia Soeng, M.Kes., PA(K)drg. Vinna Kurniawati. S, M.KesProf. dr. Wahyuni Lukita Atmadja, Ph.D